2020
DOI: 10.29333/iji.2020.13257a
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Metacognitive Strategies Implementation on Students’ Reading Comprehension Achievement

Abstract: Metacognitive strategies are known to be important in improving reading achievement. This study investigated whether there was any significant difference on students' reading comprehension achievement score by using metacognitive strategies and investigated what metacognitive strategies implemented on students' reading comprehension achieving. All participants of this study were students in the eleventh grade of Senior High School. The data were collected by means of Reading Comprehension Test (RCT) and Metaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 13 publications
4
63
0
3
Order By: Relevance
“…For instance, several researchers determined the association of reading instruction and reading performance (Aka, 2019;Jabri et al, 2020). Moreover, research was conducted on association between usage of reading strategies and reading achievement (Ajideh, 2019;Alshumaimeri, 2017;Muhid et al, 2020). Also, the influence of computer-assisted language learning on reading achievement was determined (Khezrlou, Ellis, & Sadeghi, 2017).…”
Section: Reading Comprehension Performancementioning
confidence: 99%
“…For instance, several researchers determined the association of reading instruction and reading performance (Aka, 2019;Jabri et al, 2020). Moreover, research was conducted on association between usage of reading strategies and reading achievement (Ajideh, 2019;Alshumaimeri, 2017;Muhid et al, 2020). Also, the influence of computer-assisted language learning on reading achievement was determined (Khezrlou, Ellis, & Sadeghi, 2017).…”
Section: Reading Comprehension Performancementioning
confidence: 99%
“…Metacognitive strategies are also essential in English reading, as noted by Muhid et al [43] in their study with 50 students showed significant results that metacognitive strategies had on reading performance, several strategies were worked on, but the most used was selective attention and the least used was self-reflection. In the same sense, Gutiérrez and Ruíz [44] investigated the effects of training in metacognitive reading strategies in two educational contexts of Spanish students, the group that carried out the strategic training obtained better scores, highlighting the importance of strategies in the understanding of The texts.…”
Section: Resultsmentioning
confidence: 78%
“…Por otro lado, a decir de Chablé (2020) afirma que la comprensión lectora, tiene una relación directa con el uso de ciertas estrategias siendo las más resaltantes las metacognitivas, por cuanto permite una reflexión continua del lector, al interactuar con los textos. De igual Muhid, et al (2020) cuyos resultados indicaron que "las estrategias metacognitivas tuvieron un efecto positivo en el rendimiento en lectura de los estudiantes".…”
Section: Solórzano Y López (2019)unclassified